Mediasi Dan Moderasi Determinan Kecurangan Laporan Keuangan Dengan Intellectual Capital Dan Manajemen Laba - Achmad Ridwan; Syahril Djaddang; Ardiansyah Syam (FEB Universitas Sultan Ageng Tirtayasa, 2020)
Financial reports are an important component for investors, but fraudulent financial statements can mislead investors in decision making. The purpose of this research is to obtain empirical evidence in a fraud pentagon consisting of Pressure and Opportunity to detect fraudulent financial stataments indicated by using the Beneish M Score. The sample of this research consists of 54 companies in 2015-2017 with 20 companies doing fraud. The analysis technique used is Partial Least Square. The results and conclusions showed that pressure (at proxy financial stability and ROA) has significant effect to fraudulent financial statement while opportunity (at proxy ineffective monitoring) don’t have significant effect. Meanwhile, pressure and opportunity was when the moderated with earning management and mediated with intellectual capital has significant effect to fraudulent financial statement at Infrastructure and Utility Companies listed BEI in Indonesia.